Innovative Thought of Critical Ethnography in the Dominance of Excellent Theory in the Research and Practice of Public Relations - Kriyantono, Rachmat (Tuturlogi: Journal of Southeast Asian Communication, 2020)
This study aims to describe the critical ethnographic approach as innovative thinking in the study and practice of public relations amid the dominance of excellent theory. The importance of promoting this approach is also driven by the desire that public relations studies and practices are not fixed on just one type of paradigm, but other paradigms must be developed to enrich the study of Public relations. By reviewing 20 literature, books and journal articles, the author reveals some criticism of the excellent theory, a dominant theory in public relations research and practices. The excellent theory, which is called a normative model, is perceived difficult to apply to different organizational conditions, therefore, there is an assumption that the model is only utopian. The symmetric model is too focused on communication between organizations and the public so that it pays little attention to aspects of relationships. Some critics offer new approaches that based on the view that the practice and study of public relations should not be limited to placing public relations activities as a value-free entity and based on certain systematics and standards to guarantee its objectivity. This view leads to offer a critical ethnography to be adopted in public relations research and practices.